2020
DOI: 10.1021/acsomega.0c00381
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical Properties of Fluorescent Self-Assembled Peptide Nanostructures for Singlet Oxygen Generation

Abstract: In this work, a drug delivery system for perillyl alcohol based on the peptide self-assembly containing 3-(2benzothiazolyl)-7-(diethylamino)coumarin (C6) as a fluorescent additive is obtained, and its photophysical characteristics as well as its release dynamics were studied by steady-state and time-resolved fluorescence spectroscopy. Results proved the dynamics of drug release from the peptide nanostructures and showed that the system formed by the self-assembled peptide and C6, along with perillyl alcohol, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Phe-Phe/C6 fluorescence lifetime decrease evidences that energy is being transferred from its single electronic excited state to molecular O 2 , which, is a triplet state. Although it is a process with a low probability of occurring, because it involves electronic excited states with distinct spin multiplicities, it is the way most likely to generate O2 singlet, an instable compound that find several applications, mainly in photodynanic therapy, as we showed in a previous work [34]. The assessment of the mechanisms in which O 2 determination is possible, also enables to understand the system and prospect further studies and applications.…”
Section: Fluorescence Lifetime Measurementsmentioning
confidence: 88%
“…Phe-Phe/C6 fluorescence lifetime decrease evidences that energy is being transferred from its single electronic excited state to molecular O 2 , which, is a triplet state. Although it is a process with a low probability of occurring, because it involves electronic excited states with distinct spin multiplicities, it is the way most likely to generate O2 singlet, an instable compound that find several applications, mainly in photodynanic therapy, as we showed in a previous work [34]. The assessment of the mechanisms in which O 2 determination is possible, also enables to understand the system and prospect further studies and applications.…”
Section: Fluorescence Lifetime Measurementsmentioning
confidence: 88%
“…A variety of PS carriers have been investigated such as metal–organic frameworks and biopolymer micro- or nanoparticles, but these carriers required complicated, long synthetic procedures. , In the literature, there are very few reports in which a mixture of solvents was used for the PDT delivery system. Albino de Souza et al studied peptide-based self-assembly in ethanol/water (E/W) 1:1 for 1 O 2 generation . Kessel and co-workers have also examined tin etiopurpurin (SnET 2 ) ethanol-soluble drug delivery through a water-soluble cyclodextrin derivate as a delivering agent …”
Section: Introductionmentioning
confidence: 99%
“…Albino de Souza et al studied peptide-based self-assembly in ethanol/water (E/W) 1:1 for 1 O 2 generation. 20 Kessel and co-workers have also examined tin etiopurpurin (SnET 2 ) ethanol-soluble drug delivery through a water-soluble cyclodextrin derivate as a delivering agent. 21 One particularly interesting drug delivery system is organic supramolecular entities containing phospholipids.…”
Section: Introductionmentioning
confidence: 99%
“…The supramolecular assembly of chromophores provides an alternative approach to modulate photophysics and afford functional hierarchical materials. Self-assembly often leads to dramatic changes in photophysics, formation of porous materials, , and can result in the emergence of new properties such as persistent radical formation. , Recently, our group reported that self-assembled benzophenones 2 – 4 (Figure ) exhibit persistent radical formation upon irradiation with UV light when in the solid-state but show no radicals in solution . Here, we examine how solid-state assembly of two benzophenone (BP) bis -urea macrocycles and two methylene-urea tethered dibenzophenones 1–4 influences the rate of radical formation, maximum quantity of radicals, and radical regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…19 The Garcia-Garibay group showed that nanocrystalline suspensions of BP favor n-type self-quenching with more electron rich BPs displaying faster rates of self-quenching. These studies defined three geometric considerations that modulate n-type self-quenching including (1) the distance (R) between BP* oxygen to the centroid of a nearby aryl ring, (2) the azimuth (Θ) angle which is defined as the angle between the oxygen atom of BP* and the projection of R, and (3) the altitude (Φ) angle which is defined as the angle between the plane in which the ketone of BP* resides and the centroid of the nearby aryl ring. 17 Assembled systems from our group enable us to probe these geometric influences and evaluate the importance of these constraints.…”
Section: Introductionmentioning
confidence: 99%